The Use of Borrowed Linguistic Terms and Comprehensiveness of Terminology Groups in Matej Cigale’s Znanstvena terminologija (1880) - Atelšek, Simon (Jezikoslovni zapiski, 2019)
Coinciding with the two-hundredth anniversary of the birth of the Slovenian lawyer and linguist Matej Cigale (1819–1889), this article presents the borrowing of linguistic terminology and a sample analysis of seven linguistic terminology groups in his Znanstvena terminologija (Technical Terminology, 1880). Attention is also drawn to some interesting terminography solutions identified in the analysis of terminology labeled as linguistic in this dictionary.